2016
DOI: 10.1038/icb.2016.105
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic sialic acid blockade lowers the activation threshold of moDCs for TLR stimulation

Abstract: Sialic acid sugars cover the surface of dendritic cells (DCs) and have been suggested to impact several aspects of DC biology. Research into the role of sialic acids in DCs, however, is complicated by the limited number of tools available to modulate sialic acid expression. Here we report on a synthetic, fluorinated sialic acid mimetic, Ac3FNeu5Ac, which potently blocks sialic acid expression in human monocyte-derived DCs (moDCs). Sialic acid blockade enhanced the responsiveness of moDCs to Toll-like receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…GD2 expression depends on the availability of GM3 and GD3, two sialic acid-carrying gangliosides that are produced by the sialyltransferases GM3 synthase and GD3 synthase, respectively (3,31). Previous studies by other groups and our own group have shown that the fluorinated sialic acid analogue Ac 5 3F ax Neu5Ac blocks sialic acid expression with high efficiency and selectivity (32)(33)(34)(35). In the present study we found that this fluorinated sialic acid analogue is also a potent inhibitor of GD2 expression, consistent with previous data using sialidase (40).…”
Section: Boosting Gd2 Expression In Neuroblastomasupporting
confidence: 93%
See 1 more Smart Citation
“…GD2 expression depends on the availability of GM3 and GD3, two sialic acid-carrying gangliosides that are produced by the sialyltransferases GM3 synthase and GD3 synthase, respectively (3,31). Previous studies by other groups and our own group have shown that the fluorinated sialic acid analogue Ac 5 3F ax Neu5Ac blocks sialic acid expression with high efficiency and selectivity (32)(33)(34)(35). In the present study we found that this fluorinated sialic acid analogue is also a potent inhibitor of GD2 expression, consistent with previous data using sialidase (40).…”
Section: Boosting Gd2 Expression In Neuroblastomasupporting
confidence: 93%
“…The availability of GM3 and GD3 is therefore ratelimiting for GD2 synthase activity and the production of GD2 (3,31). We and others have shown previously that a cell-permeable fluorinated sialic acid analogue, Ac 5 3F ax Neu5Ac, inhibits sialyltransferases and blocks ␣2,3 and ␣2,6 sialylation in human cells (32)(33)(34)(35). Here we investigated whether Ac 5 3F ax Neu5Ac is capable of blocking the production of the disialoganglioside GD2 in human neuroblastoma cell lines.…”
Section: Ac 5 3f Ax Neu5ac Blocks Gd2 Expression In Neuroblastoma Celmentioning
confidence: 94%
“…Using standardized flow cytometry protocols as described previously, cells were stained for different membrane markers using regular antibodies as well as with lectins and recombinant Siglec-Fc chimeras to determine their sialic acid composition [ 11 , 28 ]. To exclude dead cells, the cells were stained with fixable viability dye eFluor 780 (eBioscience, Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, sialic acid binding to Siglec-2 on B cells has been shown to suppress B-cell activation and induces tolerance to membrane antigens [ 26 , 27 ]. Furthermore, we have recently shown that monocytic cell activation can be dampened via Siglec-3 triggering [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD33rSiglecs have immune receptor, tyrosine-based inhibitory motifs, and signal negatively [18]. Interaction with Siglec-7 has the potential to also affect monocyte migration and function [19] along with T-cell activation [8, 20, 21]. During B cells activation and germinal center formation (GC), Siglecs are important for appropriate activation of B cells and responses to T-cell-dependent and independent antigens [22].…”
Section: Introductionmentioning
confidence: 99%